Бронзовые крестовидные ворварки как хроноиндикатор скифских погребений Северного Причерноморья второй — третьей четверти IV в. до н. э. - Полин, С.В.; Дараган, М.Н. (Археологія і давня історія України, 2019)
В скифских погребениях Северного Причерноморья найдена 31 бронзовая крестовидная ворварка,
преимущественно в мужских захоронениях и значительно реже в женских. Эти ворварки использовались в качестве застежек колчана и для крепления колчана к поясу. Зона концентрации находок крестовидных ворварок — Нижнее Поднепровье.
По-видимому, здесь же они и изготавливались и, вероятнее всего, на Каменском городище. Отсюда
они расходились на юго-восток до Сиваша на зимние пастбища, значительно далее на север — в лесостепь (совр. Черкасская и Киевская обл.) и на запад вплоть до Дуная. Крестовидные ворварки являются надежным хронологическим индикатором скифских погребений второй—третьей
четверти IV в. до н. э., а также отчасти и этническим. In the Scythian kurgans of the IVth century BC in the
Northern Black Sea region, 31 bronze cruciform plaques were found. Such plaques are found mainly in male
graves and much less often in female ones. These plaques were used as quiver buckles and for attaching the quiver
to the belt. The main zone of concentration of crossshaped plaques finds covers is the territory of the Lower
Dnieper region, directly to the Dnieper. Apparently, this indicates that they were made in this region, where their
place of manufacture could be only Kamenskoe hillfort, which was the center of metallurgy and metalworking in
Steppe Scythia. From here they diverged south-east to Sivash within the present-day Kherson region, and much
further north to the forest-steppe within the presentday right-bank Cherkasy and left-bank Kiev regions.
Cross-shaped plaques are indicators of the advance of the steppe Scythians from the Lower Dnieper region to
the north in the Ukrainian forest-steppe, to the west as far as the Lower Danube and very close to the south-east
to Sivash. The latter direction, apparently, corresponds to migrations to winter pastures. More than half of all
finds of cross-shaped plaques reliably date from within the second to third quarters of the IVth century BC, which
gives every reason to assume the same dating for the complexes, where there are no own dating materials. In
general, such bronze cross-shaped plaques are a reliable chronological indicator Scythian burials of the Northern
Black Sea region of the second — third quarter of the IVth century BC, and also partly ethnic.